Drivers of China's foreign direct investment into Africa - Braga de Macedo, Jorge (2014)
We assess the determinants of Chinese direct investment in Africa compared with those of global FDI. We find that economic size and macroeconomic stability are positively correlated with Chinese and global FDI in Africa. Institutional variables, such as accountability and rule of law, are not significant in either case and the same can be said about FDI-aid complementarities. The presence of oil is a determinant of Chinese FDI but not of global FDI into Africa. Conversely, the openness of the economy is a determinant for global FDI but not of Chinese FDI, which appears to favour closed economies possibly due to industrial organizational concerns. While these differences accord with intuition, we find no evidence for the claim that Chinese FDI in Africa is related to non-economic governance in a specific way that differs from global practice. More refined governance indicators should be used to verify whether Chinese and global FDI into Africa remain indistinguishable on this score: we plan to do this in future research.